International transmission of stock market movement: evidence from the Islamic Equity Markets - Ruzita Abdul Rahim; Mohammed Zain Yusof; Ros Zam Zam Sapian; Hawati Janor (Penerbit Universiti Kebangsaan Malaysia, 2008)
This study examines whether the widely accepted conclusion from the generic equity markets, that the emerging equity markets remain segmented from the world markets but exhibit strong intra-regionalleaderships. is also supported from Islamic equity market viewpoint. The new evidence is ,sought through investigating the relationships between Malaysia and most important players in world equity markets, namely the US, the UK, Japan, and Canada as well as the Asia Pacific and several world equity markets. This study utilizes macro levels data of daily closing price index of the Dow Jones Islamic Market (DJIM) indexes from the most recent period of 1999:06 to 2007:06. Using Granger-causality and multiple time series regression tests, it investigates the chain of information leadership within the universe of Malaysia and the rest of the selected markets. The results indicate that the stock prices at time t in Malaysian Islamic equity markets can be better predicted by incorporating information transmitted from the Asia Pacific region (excluding Japan) and World Emerging markets at time t-I and from World Developed markets including the us at time t-5. As for Japan, this market consistently fails to show any significant role in explaining returns on stocks traded in Malaysian Islamic markets.